Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd011995
|View full text |Cite
|
Sign up to set email alerts
|

Saline irrigation for chronic rhinosinusitis

Abstract: Analysis 2.2. Comparison 2 Intranasal steroids versus nasal saline (nebulised, small-volume), Outcome 2 Adverse events. Analysis 2.3. Comparison 2 Intranasal steroids versus nasal saline (nebulised, small-volume), Outcome 3 Endoscopy scoremeasured using modified Lund-Mackay (range unknown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 17 publications
0
43
0
6
Order By: Relevance
“…The study suggested that saline irrigation using a hypertonic solution is beneficial in the short‐term treatment of CRS when used in large volumes (150 mL). However, the quality of the evidence was low . Similarly, there is moderate‐quality evidence that topical corticosteroids improve nasal blockage and high‐quality evidence that they increase the risk of epistaxis …”
Section: Discussionmentioning
confidence: 99%
“…The study suggested that saline irrigation using a hypertonic solution is beneficial in the short‐term treatment of CRS when used in large volumes (150 mL). However, the quality of the evidence was low . Similarly, there is moderate‐quality evidence that topical corticosteroids improve nasal blockage and high‐quality evidence that they increase the risk of epistaxis …”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CRS is aimed at reducing airway inflammation, and nasal steroids are the first‐line treatment, which may be combined with nasal lavage . However, other medical interventions such as montelukast and low‐dose macrolides may also have some effect, although at present there remains the need for large, randomized trials of these treatments.…”
Section: Crs and Nasal Polypsmentioning
confidence: 99%
“…Medical management is a crucial component in the treatment of CRS, both as a first‐line treatment and as a means for maintaining disease improvement after endoscopic sinus surgery. Medical management of CRS primarily consists of intranasal saline irrigations and intranasal corticosteroids as supported by level‐1 evidence . Using a multifaceted approach that includes both saline irrigations and topical intranasal corticosteroids, the sinonasal inflammation associated with CRS is decreased with a reciprocal improvement in patient outcomes …”
Section: Introductionmentioning
confidence: 99%